ANALISIS KUALITAS LAYANAN AKADEMIK DAN ADMINISTRASI TERHADAP KEPUASAN PELAJAR PADA THE LEADERSHIP INSTITUTE Pte Ltd - Githa Claudia Tobing; M. Khoiri (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Educational institutions are organizations that provide services with the aim of educating the nation's life and are expected to be sensitive to current situations and conditions. The Leadership Institute as the provider of Education services, must be able to understand and pay attention to the feelings of customers, in this case there are students. The feeling of students as customers who go through the academic service process will leave a deep impression on The Leadership Institute. This study aims to analyze how the quality of service and administration on student satisfaction at The Leadership Institute Pte Ltd. The population used was 120 respondents and all of them were sampled with the saturated sample technique. Data processing is assisted by SPSS version 25 software with quantitative methods. From the results of multiple linear regression obtained Y = 1.067 + 0.200X1 + 0.349X2. The results showed that the academic service quality variable (X1) tcount > ttable (4.135 > 1.734) and the administrative service quality variable (X2) tcount > ttable (7.029 > 1.734). Based on the test criteria if tcount > ttable, then H0 is rejected and Ha is accepted which means the quality of academic services (X1), and the quality of administrative services (X2) affect student satisfaction (Y), in which the variables of academic service quality (X1), and the quality of administrative services (X2) have a positive and significant effect on student satisfaction (Y).